Contribution of oxidative stress to endothelial dysfunction in hereditary hemorrhagic telangiectasia - Jerkic, Mirjana; Letarte, Michelle (Frontiers in Genetics, 2015)
Oxidative stress causes endothelial dysfunction and is implicated in the pathogenesis of cardiovascular diseases. Our studies suggested that reactive oxygen species (ROS) play a crucial role in Hereditary Hemorrhagic Telangiectasia (HHT) disease, a vascular dysplasia affecting 1 in 5,000-8,000 people. Mutations in endoglin (ENG) and activin receptor-like kinase (ACVRL1) genes are responsible for HHT1 and HHT2 and are associated with arteriovenous malformations. Endoglin and ACVRL1 interact with endothelial NO synthase (eNOS) and regulate its activation. Mice heterozygous for these genes (Eng+/− and Acvrl1+/-) show reduced endoglin or ACVRL1 protein levels in endothelial cells causing eNOS uncoupling, generation of reactive oxygen species (ROS) rather than nitric oxide (NO•), leading to impaired NO• mediated vasodilation. ROS production is increased in several organs of Eng+/− and Acvrl1+/− mice, including lungs, liver, and colon, affected in HHT. The major source of increased oxidative stress in these tissues is eNOS-derived ROS and not mitochondrial or NADPH oxidase-dependent ROS. Eng+/− and Acvrl1+/− mice also develop with age signs of pulmonary arterial hypertension (PH) attributable to eNOS-derived ROS, which was preventable by antioxidant treatment. To date, only one pilot study has been carried out in HHT patients, and it showed beneficial effects of antioxidant therapy on epistaxis. We suggest that more clinical studies are warranted to investigate whether antioxidants would prevent, delay or attenuate manifestations of disease in individuals with HHT, based on our experimental data in mouse models.